HAMBATAN PENEGAKAN HUKUM PIDANA TERHADAP PELAKU PERUSAKAN RUMAH ADAT SUMBA - Ezra Yohanes Godo Bili; Jimmy Pello; Ngongo Dede (Petitum Law Journal, 2026)
This research aims to identify and analyze the obstacles faced in enforcing criminal law against the perpetrator of the destruction of a traditional house in Bodo Maroto Village, West Sumba Regency a site recognized as a cultural tourism object in Sumba. The incident occurred when a man, driven by anger toward his wife, threw a kerosene lamp, unintentionally causing a massive fire that destroyed the traditional house and several surrounding homes. The research employs an empirical legal approach supported by a normative juridical analysis. Data were collected primarily through interviews with local traditional leaders and tourism stakeholders. The findings indicate that the main obstacles to legal enforcement include limited law enforcement resources, a low level of legal awareness within the community, and significant socio-economic impacts, such as community trauma and loss of tourism income. Moreover, cultural and familial considerations led the community to refrain from reporting the perpetrator to the authorities. This study concludes that legal enforcement in customary law areas requires a more contextual and collaborative approach between law enforcement agencies, local government, and indigenous communities.